Interfacial Activity of Amine‐Functionalized Polyhedral Oligomeric Silsesquioxanes (POSS): A Simple Strategy To Structure Liquids. Issue 30 (24th June 2019) - Hou, Honghao; Li, Jin; Li, Xiangming; Forth, Joe; Yin, Jie; Jiang, Xuesong; Helms, Brett A.; Russell, Thomas P.
Abstract: Amine‐functionalized polyhedral oligomeric silsesquioxane (POSS), the smallest, monodisperse cage‐shaped silica cubic nanoparticle, is exceptionally interfacially active and can form assemblies that jam the toluene/water interface, locking in non‐equilibrium shapes of one liquid phase in another. The packing density of the amine‐functionalized POSS assembly at the water/toluene interface can be tuned by varying the concentration, the pH value, and the degree of POSS functionalization. Functionalized POSS gives a higher interface coverage, and hence a lower interfacial tension, than nanoparticle surfactants formed by interactions between functionalized nanoparticles and polymeric ligands. Hydrogen‐bonded POSS surfactants are more stable at the interface, offering some unique advantages for generating Pickering emulsions over typical micron‐sized colloidal particles and ligand‐stabilized nanoparticle surfactants. Abstract : Ligand‐free POSS nanoparticle surfactants can assemble at a liquid–liquid interface and lock in non‐equilibrium shapes. Their use thus constitutes a facile alternative strategy for Pickering emulsification and structuring liquids, complementing typical approaches based on the use of colloidal microparticles and ligand‐stabilized nanoparticle surfactants.